Biodegradable polyester‐based microcarriers with modified surface tailored for tissue engineering. Issue 3 (3rd June 2014) - Privalova, A.; Markvicheva, E.; Sevrin, Ch.; Drozdova, M.; Kottgen, C.; Gilbert, B.; Ortiz, M.; Grandfils, Ch.
Abstract Microcarriers have been proposed in tissue engineering, namely for bone, cartilage, skin, vascular, and central nervous system. Although polyester‐based microcarriers have been already used for this purpose, their surface properties should be improved to provide better cell growth. The goal of this study was to prepare microbeads based on poly(d, l‐lactide) acid, poly(l‐lactide) acid, and to study cell behavior (adhesion, spreading, growth, and proliferation) in function of microbead topography and surface chemistry. To improve L‐929 fibroblasts adhesion, microbead surface has been modified with three polycations: chitosan, poly(2‐dimethylamino ethylmethacrylate) (PDMAEMA), or chitosan‐g‐oligolactide copolymer (chit‐g‐OLA). Although modification of the microbead surface with chitosan and PDMAEMA was performed through physical adsorption on the previously prepared microbeads, chit‐g‐OLA copolymer was introduced directly during microbead processing. This simple approach (1) bypass the use of an emulsifier (polyvinyl alcohol, PVA); (2) avoid surface "contamination" with PVA molecules limiting a control of the surface characteristics. In vitro study of the growth of mouse fibroblasts on the microbeads showed that both surface topography and chemistry affected cell attachment, spreading, and proliferation. Cultivation of L‐929 fibroblasts for 7 days resulted in the formation of a 3D cell‐scaffold network. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 939–948, 2015.